The influence of nurse practitioner staffing on intensive care unit mortality. Issue 3 (March 2020) - Chang, Chih-Lun; Tang, Gau-Jun; Wu, Chin-Pyng; Pu, Christy; Chen, Hsin-Chih
ABSTRACT: Background: In Taiwan, nurse practitioners (NPs) have taken on expanded clinical roles in the intensive care unit (ICU) due to insufficient staffing of attending physicians and resident physicians. Local problem: The objective of this study was to investigate the influence of NP staffing on the quality of patient care in ICUs. Methods: This is a retrospective study that selected patients from the ICUs of three hospitals during 2015. The mortality risks among the three hospitals were compared after adjusting variables using the Cox regression model. The care qualities of the three hospitals were analyzed using the standardized mortality ratio. Interventions: Hospital A consisted of attending physicians and resident physicians. Hospital B consisted of attending physicians and NPs. Hospital C consisted of attending physicians, NPs, and resident physicians. Results: Outcomes were assessed for 2, 932 patients. The patients in hospital A had a lower mortality risk than hospital B or C. Septic shock patients received better care quality in hospital B than in hospital A or hospital C. Conclusions: In regional hospitals with lower NP-to-patient ratios, increasing that ratio could reduce the risk of mortality in the ICU and increase the quality of care.